2010
DOI: 10.1007/s12080-010-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

Landowners’ ability to leverage in negotiations over habitat conservation

Abstract: Voluntary conservation agreements are commonly used to stem the impact of habitat destruction and degradation on terrestrial biodiversity. Past studies that aim to inform how resources for conservation should be allocated across land parcels have assumed the costs of securing conservation on sites can be estimated solely on the basis of the value of alternative land uses. However, in a voluntary negotiation, a landowner could hold-out for a higher payment based on a conservation group or agency's willingnessto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As has been found in other applications of conservation planning, we might expect that these rankings of smaller numbers of choices will be more robust to uncertainty in the underlying data than will absolute benefit–cost ratios. However, in the specific context of acquiring parcels for protection, this thinning in the choice set can introduce other issues and concerns (see Lennox et al . and Lennox and Armsworth).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been found in other applications of conservation planning, we might expect that these rankings of smaller numbers of choices will be more robust to uncertainty in the underlying data than will absolute benefit–cost ratios. However, in the specific context of acquiring parcels for protection, this thinning in the choice set can introduce other issues and concerns (see Lennox et al . and Lennox and Armsworth).…”
Section: Discussionmentioning
confidence: 99%
“…However, when it comes to acquisition costs, there may not be one unique value that is relevant. Instead, there can be an interval of possible acquisition costs for any given parcel, one bounded below by the current landowners’ willingness to accept (WTA) the terms of an acquisition deal and one bounded above by the conservation organization's willingness to pay (WTP) to acquire the property . A landowner's WTA will depend on their valuation of possible alternative uses of the land and the transaction costs they would face to get an agreement in place.…”
Section: Assumptions Underlying Cost Estimationmentioning
confidence: 99%
“…a & d). In our previous analysis of these issues (Lennox et al ), we found that site complementarity increases the leverage potential of landowners when compared with situations in which sites are substitutes, such as maximizing species occurrences. Taken alongside the fact that site complementarity allowed cooperatives to gain substantial amounts of surplus, it appears that recognizing complementarity can result in negative economic consequences for conservation groups.…”
Section: Discussionmentioning
confidence: 75%
“…We began to investigate these ideas in Lennox et al (), where we modeled the situation in which a conservation group prioritizes one site for protection. We then determined the maximum amount the landowner of this site could demand above her or his WTA, a value we termed the landowner's leverage potential.…”
Section: Introductionmentioning
confidence: 99%
“…It is nearly impossible to purchase B6 under Uniform prices -because of its high production value, even a modest price markup would require all plots (not adjacent to the NP) to be purchased at a very high price. This is similar to the "hold out" problem considered by Lennox et al (2012). Thus, just one high-PV plot essentially excludes complete corridors in given row.…”
mentioning
confidence: 73%